Conceptual structure analysis with Bibliometrix package in R: A scientific communication of sport education - Hafiar, Hanny; Budiana, Heru Ryanto; Mirawati, Ira; Abdullah, Khairul Hafezad; Purnomo, Eko (Retos (Madrid), 2024)
Many studies on sports education have been conducted, some of which are published and disseminated through scientific journals. Publication by scientific journals is a part of scientific communication. It demands a review of the existing research to understand the conceptual structure of certain studies, especially the time they intersect with one another, such as sports education. In the database, sport education articles are commonly categorized into the subject of Education & Educational Research and/or Sport Sciences. This study aimed to obtain an overview of the similarities and differences in the conceptual structure of sport education studies included in the subject of Education & Educational Research and Sport Sciences. It employed a database from the Web of Science using the bibliometric method. Bibliometric analysis was performed with Bibliometric Package, a Built-in R tool. One of our key findings lies in the similarities and differences between the two. We also explored some implications in the discussion section. This paper completed the existing kinds of literature with additional insights for researchers and practitioners of sports education to consider and find future research directions. The results suggested similarities and differences in mapping between the two subjects, including timespans, percentages of annual growth rate, average ages, average citations per doc, references, keywords, and international collaboration. Keywords: bibliometric analysis; conceptual structure; scientific communication; sports education; Sport Sciences.